Budgeting Management Policy in Improving the Quality of Education at SMPTQ Al Falaah Indragiri - Lyadi, Muslim; Syarif, Syarif; Hasri, Salfen; Sohiron, Sohiron (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Policy is a series of concepts that become the main line and basis of a plan in carrying out work or a way of acting in education in facing and dealing with a problem that results in a decision from all relevant stakeholders to achieve better educational goals. However, this policy often makes mistakes in education. The aim of the research in this paper is to determine the implementation of the principal's policy regarding budgeting management in improving the quality of education at SMPTQ AL FALAAH INDRAGIRI, to determine the constraints of the principal in managing budgeting in improving the quality of education at SMPTQ AL FALAAH INDRAGIRI. The approach used in this research is qualitative using qualitative descriptive. The subjects in this research were the school principal and treasurer. Research data collection techniques are using interviews, observation and documentation. The results of this research show that the principal of SMPTQ AL FALAAH INDRAGIRI has implemented good policies in managing budgeting to improve the quality of education at the school, as for what can be proven, namely in the form of varied extracurriculars and has won awards in participating in competitions by SMPTQ students. AL FALAAH INDRAGIRI. The obstacles faced by this school in managing budgeting to improve quality at this time is one of them is the lack of funds going to the AL FALAAH INDRAGIRI SMPTQ school.